(untitled) (Applied Biological Research, 2023)
A database of angiotensin-converting enzyme-2 (ACE2) and furin inhibitors were selected as ligands to screen them as drug leads against SARS CoV2. The methodology employed for screening the inhibitors entailed the use of ADMET SAR server, which facilitated the assessment of drug likeliness, absorption, distribution, metabolism, excretion, and toxicity analysis. Molecular docking analysis was done by using AutoDock Vinasoftware, and it revealed that three potential inhibitors viz., captopril, nicotianamine, and perindopril, exhibited strong binding affinity within the active site of ACE2 protein. Captopril exhibited highest binding affinity of -5.5 kcal mol-1to ACE2 protein with low dock score of -26.074. 4-hydroxycoumarin showed strongest binding with furin active site residues with a binding score of -6.8 kcal mol-1followed by scopoletin and barlerin whose binding scores were slightly lower than 4-hydroxycoumarin. All the 3 ligands showed strong hydrogen binding with conserved Trp-531. The inhibitor 4-hydroxycoumarin exhibited binding with furin involving the amino acid residues Glu-271, Gln-488, Asn-310, Pro-266, Ala-532, and Trp-531. The study revealed that ACE2 and furin inhibitors can serve as lead molecules for optimization and drug development against SARS CoV2. The study has signifi cance in the exploration and development of effective drugs against coronavirus.